Econometric Estimation of Foresight: Tax Policy and Investment in the U.S. - Steigerwald, Douglas G.; Stuart, Charles E. (The Review of Economics and Statistics, 1997)
We develop a method for measuring the foresight agents have. We first dichotomize an agent’s information at current date t into knowledge up to date t 1 f and expectations after t 1 f. We then form a residual-based test statistic that allows us to compare prediction errors for econometric models based on different values of f. We illustrate the method, examining investment around tax reforms to measure the foresight firms have about tax policy. In this illustration, current investment appears to reflect currently available information but little foresight other than foresight of enacted policy changes.